Development of Non-Spiny Brinjal from Spiny Brinjal through Conventional Breeding (Indian Journal of Arid Horticulture, 2025)
The spiny brinjal (Solanum melongena) var. VRM-1 is a familiar and promising variety in Vellore district and is commonly used for making Ennai Kathirikai, a side dish for biryani. However, the spines on the stalk pose a major challenge for picking and handling the fruits.A breeding initiative was undertaken at the Agricultural Research Station & Krishi Vigyan Kendra, Virinjipuram, to mask the spiny trait through a crossing program. The crosses aimed to develop a non-spiny brinjal while retaining desirable traits. Both parent plants used in the study were genetically pure for their respective spiny and non-spiny characteristics.A total of 18 crosses were made between spiny and non-spiny brinjal progenies. The true F1 generation was tagged in both cross combinations. In the F1 population of spiny × non-spiny crosses, 100% of the plants exhibited spiny traits. However, in the F1 population of non-spiny × spiny crosses, a reduced percentage of partially spiny plants was observed. This study confirms that the spiny trait is dominant.Further generational studies were conducted with continuous selfing. Results revealed that 100% non-spiny plants with high yield were obtained in the third and fifth cross derivatives during the fourth generation. Comparative trials were conducted during Kharif 2015 and Rabi 2015-16 with spiny brinjal VRM-1. The highest fruit yield per plant was recorded in the non-spiny × spiny third cross (1.43 kg/plant), followed by the non-spiny × spiny fifth cross (1.56 kg/plant).These genotypes could be utilized in further breeding programs to improve fruit yield and the non-spiny trait.
Keywords: Brinjal; breeding; non-spiny; conventional breeding; Solanum melongena